Caracterización de la incidencia y severidad de antracnosis (Colletotrichum lindemuthianum) (Sacc. & magnus) y mancha angular (Pseudocercospora griseola) en 17 accesiones de fréjol arbustivo (Phaseolus vulgaris L.), en la zona agroecológica de Naguán, provincia Bolívar - Gaibor Lucio, Verónica Fernanda (2023)
The bean (Phaseolus vulgaris L.) is the most important legume consumed like a grain in Ecuador. This culture had been affected by diseases. For this reason, the objectives of this study were: i) Identify the agronomic characteristics of the bean crop related to diseases. ii) Determine the incidence and severity caused by anthracnose and angular leaf spot in bean, and iii) Select the bean accession with characteristics of tolerance to the diseases evaluated. This research was carried out at the “Granja experimental Naguan” of the Universidad Estatal de Bolívar. In this study it was studied 17 bean accessions were evaluated with a Randomized Complete Block Design (RCBD) with three replications. The main results found in this research were: the incidence and severity were significant p<0.005 only for angular leaf spot, being the main disease detected in this study. Of the 17 bean accessions, the cultivars such as fréjol Canario Chillanes, INIAP 428 Canario Guarandeño, FMR1 and INIAP 482 Afro – Andino had some tolerance to angular leaf spot due to a low area under the disease curve (ABCDE Ma). In the case of yield, the treatments T5 INIAP - 430 Portilla with 2550.59 kg ha-1 showed the highest productivity. In terms of morphological characteristics, the red color was the main grain cover color (CPCG) with 35.29%, opaque with 17.64% was grain brightness (BG) and kidney-shaped with 47.05% was the most grain shape (FG). According to those results, the accessions with the best agronomic performance, adaptation, tolerance to angular leaf spot and high productivity were T5 INIAP - 430 Portilla, T9 INIAP - 480 Canario Rocha and T17 Canario Chillanes.